Effect of Al evaporation temperature on the properties of Al films grown on sapphire substrates by molecular beam epitaxy. Issue 37 (25th April 2015) - Wang, Wenliang; Yang, Weijia; Liu, Zuolian; Wang, Haiyan; Lin, Yunhao; Zhou, Shizhong; Lin, Zhiting; Qian, Huirong; Wen, Lei; Yang, Meijuan; Zhu, Yunnong; Liu, Guorong; et al.
<x xml:space="preserve">Abstract</x> The effect of Al evaporation temperature on the properties of Al films grown on sapphire substrates by molecular beam epitaxy has been studied in detail.